Pengaruh Perputaran Modal Kerja, Perputaran Total Aset, Debt To Equity Ratio, Current Ratio Dan Sales Growth Terhadap Profitabilitas Perusahaan Manufaktur Sub Sektor Kosmetik Yang Terdaftar Di BEI Periode 2019-2023 - Soliha, Jamaliyatus; Pranjoto, R.Gatot Heru (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
In the era of globalization, it is important for companies to have good financial management. For this reason, it is necessary to carry out a financial analysis to determine the company's financial performance. A company's financial performance can be measured by financial ratios. The aim of this research is to determine the effect of working capital turnover, total asset turnover, Debt to equity Ratio, Current Ratio and Sales Growth on the profitability of cosmetic sub- sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Sampling used a purposive sampling technique where from a total of 7 companies, 6 companies met the specified criteria. From the partial test results (t), working capital turnover has a negative and insignificant influence on Return on Assets (ROA), total asset turnover has a positive and significant influence on Return on Assets (ROA), Debt to Equity Ratio has a negative influence and significant on Return on Assets (ROA), Current Ratio has a negative and insignificant influence on Return on Assets (ROA), Sales Growth has a negative and insignificant influence on Return on Assets (ROA). Simultaneous test results (F) working capital turnover, total asset turnover, Debt to Equity Ratio, Current Ratio and Sales Growth influence Return on Assets (ROA).